2012
DOI: 10.1089/lap.2011.0409
|View full text |Cite
|
Sign up to set email alerts
|

Complete Versus Partial Mobilization of Splenic Flexure During Laparoscopic Low Anterior Resection for Rectal Tumors: A Comparative Study

Abstract: In our study, complete SFM decreased conversion rates, but this finding may be related to the higher rate of T4 tumors in the partial SFM group. Complete SFM assures an increase in reservoir creation in patients receiving a low anterior resection. Because other parameters are identical, the decision for the level of SFM is better left to the surgeon in cases undergoing a low anterior resection, but complete SFM may be preferred in cases who are candidates for a reservoir formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The complete option consisting of the division of the splenocolic, phrenicocolic, gastro colic and pancreaticomesocolic ligaments. In partial SFM, it is limited only to the division of splenocolic and phrenicocolic ligaments while the gastro-colic and pancreaticomesocolic attachments are not divided (9). Gezen C et al demonstrated in their study the advantages of a complete SFM especially in patients who are candidates for a reservoir formation (9).…”
Section: Discussionmentioning
confidence: 99%
“…The complete option consisting of the division of the splenocolic, phrenicocolic, gastro colic and pancreaticomesocolic ligaments. In partial SFM, it is limited only to the division of splenocolic and phrenicocolic ligaments while the gastro-colic and pancreaticomesocolic attachments are not divided (9). Gezen C et al demonstrated in their study the advantages of a complete SFM especially in patients who are candidates for a reservoir formation (9).…”
Section: Discussionmentioning
confidence: 99%
“…Also, SFM during laparoscopic AR or LAR may be associated with longer operation time, patient repositioning, additional port insertion, or splenic injury 17,18. A mail-in survey of 35 experienced laparoscopic colorectal surgeons showed that SFM is one of the hardest procedures to perform6.…”
Section: Discussionmentioning
confidence: 99%
“…The use of SFM for CRC surgery remains a contentious issue [5,6,8] , but safe dissection of the splenic flexure to fully mobilize the descending colon is mandatory not only for oncologic resection but also for safe anastomosis [4,[9][10][11] . The definition of SFM is different among several studies with some describing the technique as either complete or partial mobilization [3,5,6,12] . However, it is relevant to know the procedural aspect of SFM consisting of the division of the splenocolic, phrenicocolic, gastro colic and pancreaticomesocolic ligaments.…”
Section: Sfmmentioning
confidence: 99%
“…Laparoscopic surgery has gained increasing interest for the treatment of CRC. Laparoscopic approach for colon and rectal cancer was associated with less morbidity, enhanced recovery, and at least equivalent oncological outcomes [3][4][5][6] . In China Medical University Hospital (CMUH), a tertiary medical center in Taichung City, a team of colorectal surgeons performs a high volume of cases for laparoscopic rectal surgeries.…”
Section: Introductionmentioning
confidence: 99%